Checking and correction of drug information in the standards of care and clinical guidelines - B. K. Romanov (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2018)
Results of the checking and correction information of standards of medical care and clinical guidelines prepared by the principal non-staff specialists of the Ministry of Health of Russia from 2012 to 2015 in terms of information about medicines are presents. The results of the analysis of typical errors when prescribing medicines are summarizes. Recommendations for the prevention and elimination of errors in the preparation of information on medicinal products are presents.